2013
DOI: 10.2754/avb201382020209
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastometry used for evaluation of blood coagulability in dogs with kidney diseases

Abstract: Kidney diseases as protein-losing nephropathies are predisposing conditions for thrombosis/ thromboembolism in dogs due to increased blood coagulability. The aim of this study was to use thromboelastometry for investigation of changes in haemostasis in dogs affected by renal proteinuria alone or concomitant with azotemia. The study was done at 55 client-owned, healthy (n = 34), proteinuric (n = 14), and proteinuric/azotemic (n = 7) dogs. Blood coagulation was assessed by means of standard coagulation profile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“… 38 A more recent animal study also reported significant ( P < 0.05) moderate correlation between these parameters. 77 Variability in the correlation between ROTEM ® platelet component and platelet count may be attributable to the platelet component being a measure of platelet function, which may be distinct from platelet count. Similar considerations apply to TEG ® , where correlations between platelet count and TEG ® MA have been documented.…”
Section: Parameters For Assessing Platelet Contribution To Clot Strenmentioning
confidence: 99%
“… 38 A more recent animal study also reported significant ( P < 0.05) moderate correlation between these parameters. 77 Variability in the correlation between ROTEM ® platelet component and platelet count may be attributable to the platelet component being a measure of platelet function, which may be distinct from platelet count. Similar considerations apply to TEG ® , where correlations between platelet count and TEG ® MA have been documented.…”
Section: Parameters For Assessing Platelet Contribution To Clot Strenmentioning
confidence: 99%
“…Hypoalbuminemic dogs are a type of patients in which natural or synthetic colloids are frequently used to support the COP. These patients have also a high risk to form venous and arterial thrombi, and some studies have identified by means of ROTEM or thromboelastography (ROTEG) a hypercoagulable condition in dogs with protein losing enteropathy (PLE) or nephropathy (PLN) [ 24 27 ]. The hypothesized mechanism at baseline of this prothrombotic condition is a loss of proteins (from the kidney or the gut), which implies the loss of anticoagulant factors such as antithrombin [ 28 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anemia is a common complication in CKD due to deficiencies of erythropoietin and iron (FALCO et al, 2013). In HDG, blood loss during dialysis reduces Table 1 -Clinical values (average ± standard deviation) of red blood cell (RBC) count (× 10 6 µL -1 ), hematocrit (%), hemoglobin, and total platelet count (× 10 3 mm -3 ) of animals in the control group (CG) and the hemodialysis group (HDG) before (PRE) and after (POST) treatment (Day 1 to Day 15).…”
Section: Resultsmentioning
confidence: 99%